2007
DOI: 10.1210/me.2007-0160
|View full text |Cite
|
Sign up to set email alerts
|

Heterooligomerization between Vasotocin and Corticotropin-Releasing Hormone (CRH) Receptors Augments CRH-Stimulated 3′,5′-Cyclic Adenosine Monophosphate Production

Abstract: In birds, ACTH release from the anterior pituitary gland during stress is controlled by CRH and arginine vasotocin (AVT). Using 5-wk-old male chicks, simultaneous iv injections of CRH and AVT were found to result in a greater than additive increase in plasma corticosterone levels compared with that obtained with individual administration of either peptide hormone. In order to investigate molecular mechanisms underlying this observation, the chicken CRH receptor (CRHR) and vasotocin VT2 receptor (VT2R) were fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…17 Moreover, it was demonstrated that human V1bR and CRHR1 can form constitutive homoand heterodimers. 26 An atomic-force microscopy analysis of native retinal disk membranes has revealed an organization of molecules of the prototypic GPCR rhodopsin in paracrystalline arrays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Moreover, it was demonstrated that human V1bR and CRHR1 can form constitutive homoand heterodimers. 26 An atomic-force microscopy analysis of native retinal disk membranes has revealed an organization of molecules of the prototypic GPCR rhodopsin in paracrystalline arrays.…”
Section: Discussionmentioning
confidence: 99%
“…17 The logical next step to extend this observation would be to find the dimerization interfaces between the two receptors. The three-dimensional architectures of VT2R and CRHR have not been solved, as GPCRs are inherently hard to crystallize due to their relatively insoluble, lipophilic TM regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In birds, the amount of CORT that can be elicited by various HPA stimulants provides a measure of HPA sensitivity (Kuenzel and Jurkevich, 2010;Mikhailova et al, 2007;Spelman et al, 1995). We used the protocol of Spelman et al (Spelman et al, 1995) to test for adrenal sensitivity with an intravenous (i.v.)…”
Section: Studymentioning
confidence: 99%